Electrical conductivity of sintered LSM ceramics - Marinšek, Marjan (Materiali in tehnologije, 2009)
The carbonate co-precipitation route was applied for batch Lasub{0.85}Srsub{0.15}MnOsub{3} (LSM) preparation as an alternative synthesis method to the solid-state reaction. Because co-precipitation is a wet-chemistry solution process, the maximum LSM homogeneity was achieved. The microstructural characteristics, such as the porosity and grain size of the prepared LSM elements, were controlled by subjecting the green bodies to various sintering conditions. The LSM sintered bodies with relative sintered densities as high as 95 % were prepared at sintering temperatures not higher than 1100 °C. The microstructure of the prepared LSM was characterized by digital online image analysis and the microstructural parameters were determined for the ceramic phase as well as for the porosity. The electrical characteristics of the sintered LSM elements were, for the first time in the literature, described with respect to a model for the sine-wave approximation of the conductivity change for porous materials. The observed results of the relative conductivity sigma/sigmasub{0} vs. the relative density rho/rho{0} dependence were essentially consistent with the sine-wave approximation. As an absolute value, the highests sigma = 65 S/cm at 800 °C was measured for a sample with rho/rho{0} = 99.58 %.
Keywords: keramika; ceramic; koprecipitacija; lantanov stroncijev manganit; mikrostruktura; električna prevodnost